TỔNG HỢP POLYANILIN HÒA TAN ĐƯỢC TRONG NƯỚC - Huy, Vũ Đình; Minh Học, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
In present study the preparation of water soluble polyaniline (sulphonate polyaniline = SPANi) by chemical method has been described. A three stage model for the formation of SPANi was carried out: In the first stage the emeraldine salt (ES) was synthesized by chemical oxidative polymerization with ammonium persulfate as an oxidant. In the second stage the emeraldine salt deprotoned by ammonium hydroxide solution to give emeraldine base (EB). In third stage SPANi was synthesized by reaction of emeraldine base with fuming sulfuric acid. The resulting SPANi was entirely soluble in water, and no precipitation was observed for a prolonged period of time. The obtained derivatives (ES, EB and SPANi) were characterized by infrared spectrum.